LEAPing through the looking glass: secondary analysis of the effect of skin test size and age of introduction on peanut tolerance after early peanut introduction. Issue 8 (22nd March 2017) - Greenhawt, M.; Fleischer, D. M.; Chan, E. S.; Venter, C.; Stukus, D.; Gupta, R.; Spergel, J. M.
Abstract: Background: In the Learning Early About Peanut Allergy (LEAP) study, early peanut introduction in high‐risk 4‐ to 11‐month‐olds was associated with a significantly decreased risk of developing peanut allergy. However, the influences of key baseline high‐risk factors on peanut tolerance are poorly understood. Methods: Secondary analysis was conducted on the publically available LEAP dataset, exploring relationships between peanut tolerance, baseline peanut/egg sensitization, eczema severity/duration, age of introduction, gender, and race. Results: A multiple logistic regression model predicting odds of successful oral food challenge (OFC) at 60 months noted higher odds with early introduction (OR 9.2, P < 0.001, 95% CI 4.2–20.3), white race (OR 2.1, P = 0.04, 95% CI 1.1–3.9), and advancing age (OR 4.8, P = 0.04, 95% CI 1.1–20.8). Odds of peanut tolerance were lower with increasing peanut wheal size (OR 0.58, P < 0.001, 95% CI 0.46–0.74), increased baseline SCORAD score (OR 0.98, P = 0.04, 95% CI 0.97–1), and increased kUA /l of egg serum IgE (sIgE) (OR 0.99, P = 0.04, 95% CI 0.98–1). The probability of peanut tolerance in the early introduction group was 83% vs 43% in the avoidance group with SPT wheal of <4 mm. The probability of a successful OFC was significantly higher with peanut introduction between 6 and 11 months than at 4–6 months. Increasing eczema severity had limited impact on the probability of peanut tolerance in the early introduction arm. Conclusion: Increasing peanut wheal size predicted peanut tolerance only in the avoidance arm. Peanut introduction between 6 and 11 months of age was associated with the highest rates of peanut tolerance, questioning the 'urgency' of introduction before 6 months.